Wind Turbine Aerodynamics II - Shen, Wen Zhong; Shen, Wen Zhong (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue is a collection of the latest research articles on various topics related to wind turbine aerodynamics, which includes wind turbine design concepts, tip loss correction study, wind turbine acoustics modelling, and the vertical axis wind turbine concept.
English
Keywords: Technology: general issues; wind turbine aerodynamics; actuator disc; AD/NS; tip loss correction; blade element momentum; orthopter; vertical axis wind turbine; power coefficient; torque coefficient; shear flow; wind tunnel; CFD; delayed detached-eddy simulation; wind turbine; tilt angle; unsteady aerodynamics; computational fluid dynamics; wind tunnel experiment; wind turbine airfoil; turbulence; Gurney flap; aerodynamic characteristics; aeroacoustics; noise modelling; noise control; coned rotor; aerodynamics; n/a